Literature and psychology : writing, trauma and the self - Çakirtaş, Önder (Cambridge Scholars Publishing, 2019)
This volume provides a thorough study of how psychological messages are portrayed and interpreted via the written word. It explores the interactions between text and reader, as well as affiliations within the text, with particular emphasis on emotion and affect. Featuring relevant coverage on topics such as literary production, psychology in literature, identity/self and the other, and trauma studies, the book offers an in-depth analysis that is suitable for academicians, students, professionals, and researchers interested in discovering more about the relationship between psychology and liter.